Pelaksanaan Sustainability Report Berdasarkan GRI Standards Guidelines Pada Perusahaan Manufaktur di Indonesia - Widya Ananda; Hafid Aditya Pradesa; Reni Wijayanti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The primary objective of this study is to conduct an analysis of sustainability reports based on the GRI Standard Guidelines among manufacturing companies listed on the Indonesia Stock Exchange (IDX). The study focuses on sustainability reports for the years 2019-2021, which were consecutively published on the official websites of the selected manufacturing companies. Employing a purposive sampling technique, a total of 21 manufacturing companies were included in the study, covering three distinct research periods, thereby resulting in the analysis of 63 data units. The research methodology involves descriptive statistics and utilizes quantitative content analysis methods. The findings of this study reveal that, during the 2019-2021 timeframe, none of the manufacturing companies listed on the IDX have provided comprehensive disclosure of all 89 GRI Standard indicator items in their sustainability reports. Furthermore, when categorizing the implementation levels of sustainability reports as